Inverting gas-surface interaction parameters from Fourier drag-coefficient estimates for a given atmospheric model. Issue 4 (15th August 2021) - Ray, Vishal; Scheeres, Daniel J.; Pilinski, Marcin
Abstract: Satellite drag-coefficient is a highly dynamic parameter that captures the physics of the interactions between the atmosphere and the satellite surface. Physical models, known as Gas-Surface Interaction Models (GSIMs), can be used to compute the time variations in the drag-coefficient in orbit. But many input parameters to such models are not known accurately, that consequently introduce uncertainties in the drag-coefficient. This work outlines a framework to invert GSIM parameters from estimates of the drag-coefficient that are obtained during orbit determination, under the assumption of a known atmospheric density. The Fourier drag-coefficient models, developed previously by the authors, are used to model the drag-coefficient in the filtering methodology. These models allow estimation of higher-order frequencies in the drag-coefficient that are functions of the orbital and satellite attitudinal variations. In this work, it is demonstrated that information about the GSIM parameters can be obtained from estimated Fourier drag-coefficients. To that end, an extensive observability analysis of the Fourier drag-coefficient models is carried to determine the coefficients that can be estimated from tracking data.